“Cradle to Grave: An Examination of Demographic Behaviour on Two British Columbian Frontiers” - Belshaw, John (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1994)
AbstractThis paper begins an exploration of British Columbia's historical demography. It assesses rates of nuptiality and marital fertility in two turn-of-the-century cities, Nanaimo and Kamloops. Numerical male dominance is considered, along with the likelihood of high rates of nuptiality on the "frontier". The findings indicate a greater role for non-native women in early far west communities, and a greater range of options outside marriage in some locales. Fertility rates are described as well, revealing connections between natural increase and local economic factors. The study also identifies a large dependent population in the new cities and considers the effects this demographic and cost element would have had on British Columbia life.